Collaboration Technology for Rural Health-care - Raman, R. S.; agannathan, V.J; Srinivas, K.; Reddy, S.; Cleetus, K.J.; Reddy, R. (Yearbook of Medical Informatics, 1997)
Health-care is a collaborative endeavor involving a number of individuals and organizations with diverse perspectives. Computer-supported collaboration technologies have great potential to enable health-care providers to improve the quality of care provided to their patients. Such technologies have the potential to overcome barriers to quality health-care in the small, scattered populations of rural areas. Rapid changes in technology are making it more and more possible for collaborative telemedicine to be a part of the practice of medicine. The World Wide Web has amply demonstrated that the globe has shrunk and information from afar is a mere mouse click away. However, the ease with which information is accessed along with the potential disclosure and misuse of personal information has raised serious concerns about the ability to restrict such information to legitimate accesses by duly authorized health-care providers. The authors present their experience in developing a health-care collaboration facility, ARTEMIS, which enabled Web-based access to electronic medical records, and provide a vision of their experiment to provide secure telemedicine for rural health-care practitioners.
Keywords: Telemedicine; Computer-based Patient Records; Confidentiality of Electronic Health Information; Collaboration Technology